#### Answer

$f^{-1}(x) = \frac{x - 5}{3}$

#### Work Step by Step

f(x) = 3x + 5
y = 3x + 5
y - 5 = 3x
$\frac{y - 5}{3} = x$
$\frac{x - 5}{3} = f^{-1}(x)$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \frac{x - 5}{3}$

f(x) = 3x + 5
y = 3x + 5
y - 5 = 3x
$\frac{y - 5}{3} = x$
$\frac{x - 5}{3} = f^{-1}(x)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.